2018
DOI: 10.1002/jcb.27721
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐218 regulated cardiomyocyte differentiation and migration in mouse embryonic stem cells by targeting PDGFRα

Abstract: MicroRNAs (miRNAs) have been identified as key players in cardiogenesis and heart pathophysiological processes. However, many miRNAs are still not recognized for their roles in cardiomyocytes differentiation. In this study, we evaluated the effects of microRNA-218 (miR-218) in cardiomyocyte differentiation of the mouse embryonic stem cells (ESCs) in vitro. The percentage of the beating embryoid bodies (EBs) in miR-218 mimic-treated cells was reduced to 32% compared with miR-218 mimic negative control (56%) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Overexpression of miR-218 in zebrafish embryos can inhibit the normal development of heart [20, 21]. Overexpression of miR-218 can also inhibit the differentiation of mouse embryonic stem cells into mesoderm and cardiomyocytes [22]. Therefore, we speculate that miR-218 is associated with MI.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of miR-218 in zebrafish embryos can inhibit the normal development of heart [20, 21]. Overexpression of miR-218 can also inhibit the differentiation of mouse embryonic stem cells into mesoderm and cardiomyocytes [22]. Therefore, we speculate that miR-218 is associated with MI.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that miR-140-5p can limit the suppression of adipogenesis-related gene expression and intracellular lipid accumulation by PDGFRα, thus contributing to adipogenesis. Consistent with this idea, PDGFRα is involved in the differentiation of cardiomyocyte differentiation (Xu et al, 2019). However, the signaling pathway in response to PDGFRα activation is still largely unknown, and thus the molecular processes regulating the expression and function of adipogenesis-related genes remain to be further investigated in future research.…”
Section: Discussionmentioning
confidence: 85%
“… 36 , 37 On the other hand, other groups have published that PDGFRα is important for stem/progenitor cell differentiation, in particular into α‐SMA‐expressing cells or fibroblasts. 13 , 38 , 39 , 40 These putative conflicting roles of PDGFRα might originate from the type of progenitor/stem cells used. We previously showed that CD34 + /PDGFRα + /PW1 + cells differentiate toward terminally differentiated smooth muscle myosin heavy chain + SMCs, 3 which might not be the case for the stem cells used in other studies.…”
Section: Discussionmentioning
confidence: 99%